Mudskipper fishing in the coast of Bhavnagar, Gulf of Khambhat, Gujarat, India - Kanejiya, Jignesh; Solanki, Devendra; Beleem, Imtiyaz; Gohil, Bharatsinh (Journal of Fisheries, 2017)
Coastal areas of Bhavnagar district harbors wide range of ichthyofaunal diversity and diverse fisheries resources. The fishermen in this area use wide range of fishing methods and gears, which evolved traditionally and being adept extensively in Bhavnagar coastline. Livelihood of these fishermen is almost entirely depends on mudskipper fishing and they employ three types of fishing methods to catch them i.e. direct catch through digging the burrow, stick traps around mudskipper holes, and by nylon net. Fishing by using nylon net is the most commonly used method compared to others.